2016
DOI: 10.30525/2256-0742/2016-2-2-32-39
|View full text |Cite
|
Sign up to set email alerts
|

Threats and Benefits of Exchange Rate Regimes for Ukraine in Terms of European Integration

Abstract: The purpose of the paper is to determine threats and benefits of exchange rate regimes in terms of the integration of Ukraine into the European community. Emphasizing features of the manifestation of currency exchange rate in Ukrainian practice is a precondition for choosing the optimal exchange rate regime for Ukraine, which, in its turn, will provide an opportunity to reduce inflation and implement effective tools of monetary and fiscal policies to promote further economic growth and competitiveness of the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Analysis of recent research and publications. Although Ukraine's exchange rate has been studied in recent years in terms of the wider impact on the economy and a more broader discussion on the method of management of the exchange rate itself, for example see [1][2][3][4][5], very little analysis of the impact of Ukraine's exchange rate on trade specifically has been undertaken. Prior to 2014, both practical and theoretical literature focused on the effects of artificially maintaining the exchange rate such as Vorobyov [6] who used PPP method of real exchange rate to show that the UAH was overvalued and adversely affected the macro-economic fundamentals, including trade balance but concluded that although devaluation was necessary, social consequences may lead to further supporting currencies rather than devaluing (as in the case of Argentina and Brazil) and therefore, there is a need to study the wider effects of devaluation first before embarking on such policies.…”
mentioning
confidence: 99%
“…Analysis of recent research and publications. Although Ukraine's exchange rate has been studied in recent years in terms of the wider impact on the economy and a more broader discussion on the method of management of the exchange rate itself, for example see [1][2][3][4][5], very little analysis of the impact of Ukraine's exchange rate on trade specifically has been undertaken. Prior to 2014, both practical and theoretical literature focused on the effects of artificially maintaining the exchange rate such as Vorobyov [6] who used PPP method of real exchange rate to show that the UAH was overvalued and adversely affected the macro-economic fundamentals, including trade balance but concluded that although devaluation was necessary, social consequences may lead to further supporting currencies rather than devaluing (as in the case of Argentina and Brazil) and therefore, there is a need to study the wider effects of devaluation first before embarking on such policies.…”
mentioning
confidence: 99%